A fast and robust reference current generation algorithm for three-phase shunt active power filter - Zakaria Chedjara; Ahmed Massoum; Patrice Wira; Ahmed Safa; Abdelmadjid Gouichiche (Institute of Advanced Engineering and Science, 2021)
The identification of the reference currents constitutes an important part of the control of the active power filter. This part requires an accurate estimation of the frequency, phase, and proper extraction of the load current harmonics. This makes the modeling more difficult and requests a rigorous selection of techniques to be used. For the sake of simplicity, the direct method is motivated by the need for the simplicity and flexibility than the existing techniques such as the instantaneous power theory and diphase currents method. However, this method requires a robust phase-locked loop to extract the unity voltages and a robust controller to estimate the magnitude of the source current. To this end, this paper proposes the hybrid phase-locked loop (HPLL) as a good option mainly because 1) it achieves zero phase error under frequency drifts, 2) Fast dynamic response, 3) totally block the DC offset, 4) From the control point of view, it is a type 1 control system which results in high stability margin. To the best of authors’ knowledge, the HPLL has not been used in active power filter yet. Furthermore, a neural PI regulator is used to estimate the magnitude of the source current. Simulation results show the efficiency of the proposed technique and illustrate all its interesting features. For the sake of comparison, the proposed method is compared to other advanced techniques.